Are We Causing Antibiotic Resistance with Antibiotic Abuse? A Study among Dentists - Bhuvan Deep Gupta; Insha Nissar; Akanksha Monga (International Healthcare Research Journal, 2020)
INTRODUCTION: With the invention of any new technology their comes the boon and curse both. The invention and use of antibiotics comes a problem of antibiotic resistance which is much more in extent than treating the infectious disease. Keeping this in mind the WHO in 2011 gave the theme “combat drug resistance- No action today, No cure tomorrow” which was very significant. The present study was done with the aim to know the prescription pattern of antibiotics for various dental procedures by dental practitioners. MATERIALS AND METHODS: A specially prepared questionnaire exclusively designed for the study recording all the required relevant general information and information related to antibiotic prescribing patterns was used for data collection. The questionnaire consisted of three sections. The first part of the questionnaire collected the demographic details of the study population like age, gender, Graduate or postgraduate degree, area of specialization and years of practice. In the second section the Questions related to antibiotics use in certain dental clinical procedures and conditions in apparently healthy people were asked from the participants. In the last section of the questionnaire the participants were asked about the questions related to antibiotics use for certain dental clinical procedures in medically compromised cases. RESULTS: Questionnaire response rate of 73% was recorded. The study showed Augmentin to be the first choice of antibiotic by most of the respondents. The study showed that 64% of the endodontists and 74% of the general dentists prescribed antibiotics during root canal therapy where ideally operative intervention would have sufficed. Overuse of antibiotics for routine scaling and extraction was observed. CONCLUSION: The dental profession as a whole needs to acquire a deeper understanding of the global effects of unnecessary antibiotic prescription. Antibiotics when judiciously used are precise life-saving drugs.